Caribbean agenda and self-reliance : statement and closing remarks - Nicholls, Sir Neville (CDB WildeyBB, 1996)
Comments on the annual report and CDB's performance during 1995. Looks at the Caribbean agenda and self-reliance. Highlights external developments, the general economic performance of the Borrowing Member Countries and operational issues.